Equity-incentive compensation and payout policy in Europe - Burns, Natasha; McTier, Brian C.; Minnick, Kristina (Journal of Corporate Finance, 2015)
We examine the effects of executive compensation and investor protection on payout policy in Europe. We find a negative (positive) relationship between both option and restricted stock compensation and dividends (repurchases). However, when the incentive compensation is dividend protected, dividend payouts increase. Firms in weak investor protection countries pay higher dividends consistent with maintaining a reputation for distributing excess free cash flows. However, growth firms in weak investor protection countries reduce dividends (increase repurchases) in relation to increases in equity-incentive compensation. Our results are consistent with growth firms in weak investor protection countries using equity incentives as a substitute for dividends to reduce agency costs.